2007
DOI: 10.1063/1.2776022
|View full text |Cite
|
Sign up to set email alerts
|

Correlating electrical resistance to growth conditions for multiwalled carbon nanotubes

Abstract: A correlation between growth temperature and electrical resistance of multiwalled carbon nanotubes (MWNTs) has been established by measuring the resistance of individual MWNTs grown by microwave plasma-enhanced chemical vapor deposition (PECVD) at 800, 900, and 950°C. The lowest resistances were obtained mainly from MWNTs grown at 900°C. The MWNT resistance is larger on average at lower (800°C) and higher (950°C) growth temperatures. The resistance of MWNTs correlated well with other MWNT quality indices obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In the case of positive dc bias voltage, resistance decreases with increasing dc bias voltage; the corresponding resistances for +100 and +200 V were 10.4 and 5.5 kΩ, respectively. Our previous study of the relationship between electrical resistance and CNT growth temperatures has shown that the quality indexes correlate well with differences in electrical resistance, 25 and the present results reveal a similar correlation, namely that lower quality indexes produce MWCNTs with consistently higher electrical resistance. In addition to electrical characteristics, the thermal behavior of the CNT arrays was also determined using a PA technique.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In the case of positive dc bias voltage, resistance decreases with increasing dc bias voltage; the corresponding resistances for +100 and +200 V were 10.4 and 5.5 kΩ, respectively. Our previous study of the relationship between electrical resistance and CNT growth temperatures has shown that the quality indexes correlate well with differences in electrical resistance, 25 and the present results reveal a similar correlation, namely that lower quality indexes produce MWCNTs with consistently higher electrical resistance. In addition to electrical characteristics, the thermal behavior of the CNT arrays was also determined using a PA technique.…”
Section: Resultssupporting
confidence: 86%
“…The I-V data may contain information about the defect density present in CNTs. 25 Consequently, it is reasonable to conclude that negative dc bias voltage produces higher defect densities on the CNTs; the effect is more pronounced for CNTs grown under -100 V, evidenced by the highest resistance (23.0 kΩ) observed. As the negative dc bias voltage magnitude increases to -200 V, the resistance decreases to 16.0 kΩ.…”
Section: Resultsmentioning
confidence: 94%
“…The experimental setup for acquiring I -V data of individual MWCNTs relies on a Kiethley 428 current amplifier interfaced to a laptop PC using Labview as described previously [32]. To avoid unwanted heating effects, I (V ) measurements were constrained to low bias conditions (|V | 0.1 V).…”
Section: Methodsmentioning
confidence: 99%
“…The particular growth temperature of 900°C was selected because prior studies have shown that this temperature gives the highest quality PECVD-grown CNTs. 10,11 A detailed description of the PECVD system and the relevant CNT growth conditions have been reported elsewhere. 12,13 Individual MWCNTs were randomly selected for this study.…”
mentioning
confidence: 99%